2014
DOI: 10.1590/1677-3225v13n2a04
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial infection. A retrospective evaluation of eight years

Abstract: Aim: To evaluate medical records from patients who had maxillofacial infections between August 2002 and May 2010. Methods: Analysis of 157 patients' data looking for epidemiology, causes of the infection, type of treatment established and complications. Results: 113 patients had odontogenic infections and 44 had non-odontogenic infections. The white ethnicity was the most affected (64.33%), prevailing the men (53.5%). The odontogenic infections occurred mostly at the mandible (55.74%), involving the posterior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 21 publications
6
17
0
2
Order By: Relevance
“…The most commonly encountered orofacial infections were odontogenic in origin (62%), may be because most odontogenic infections arise from dental caries and periodontal disease which are associated with poor oral hygiene. This is in agreement with Chow et al, 12 who mentioned that dental caries, gingivitis and periodontitis are prevalent in the general population, and Read-Fuller et al, 13 who showed that 79% infections had an odontogenic origin, as well as Veronez et al, 14 who reported that 113/157 cases had an odontogenic cause, while only 44 patients presented a non-odontogenic infection. The cause may be due to a delay in treatment due to the relatively high cost of dental care and public indifference to dental health.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The most commonly encountered orofacial infections were odontogenic in origin (62%), may be because most odontogenic infections arise from dental caries and periodontal disease which are associated with poor oral hygiene. This is in agreement with Chow et al, 12 who mentioned that dental caries, gingivitis and periodontitis are prevalent in the general population, and Read-Fuller et al, 13 who showed that 79% infections had an odontogenic origin, as well as Veronez et al, 14 who reported that 113/157 cases had an odontogenic cause, while only 44 patients presented a non-odontogenic infection. The cause may be due to a delay in treatment due to the relatively high cost of dental care and public indifference to dental health.…”
Section: Discussionsupporting
confidence: 89%
“…Our data regarding anesthesia used is similar to Veronez et al [14] who reported 63% of cases were managed under local anesthesia and 37% required general anesthesia for the surgical treatment, due to possible risks associated with general anesthesia in addition to additional costs and time.…”
Section: Discussionsupporting
confidence: 83%
“…Our study revealed a higher frequency of the females than males 56% female to 44% male so the female to male ratio is about 1.25:1. However, the difference was not significant indicating that gender may not be considered as a determinant factor in the prevalence of orofacial infections and this accepted with R Sánchez et al [13], who stated that the two genders were equally represented in our study, and Marina et al [14], who stated that there was no significant gender difference for clinic visit rate due to orofacial infections in this study cohort (20), however Bruno Veronez et al [15] reported that in this study, men were more affected (53.33%) and this may be due to men less care about their oral hygiene. In this study show that the most common microorganism associated with orofacial infections was Streptococcus pyogen (59%), which is gram positive aerobic bacteria, this agreed with recent studies of Celakovsky P et al [16], who recorded that Streptococcus pyogenes was the most commonly isolated bacterium, also Min Kyoung Kim et al [11], reported that most bacterial isolates in the present group were Streptococcus species (54%), and Poeschl et al [10], due to Streptocoocus is most common commensal oral flora, in our study Klebsiella (10%) was the second bacteria isolated this goes with Santosh et al [1] found that the most common organisms isolated from aerobic bacteria were Streptococcus viridians 24 (36.4%), followed by Klebsiella 18 (27.3%), this is may be due to as the infection spread to secondary space or deep neck space, while this is contrast to Ingo Sobottka et al [17] who reported that anaerobic bacteria were the most commonly isolated organism in odontogenic infections, this difference may be attributed to the method of obtaining the sample for culture and sensitivity test.…”
Section: Discussionsupporting
confidence: 57%
“…Fossa canina abscess is one type of odontogenic infection that has several trigger factors that may be associated with dental caries, periapical or periodontal abscess, pericoronitis, pulpitis, or osteitis. 5,6 Orofacial infection can spread several ways, such as directly through the tissues, through the lymphatic system to the regional lymph nodes and into the bloodstream, or directly through the bloodstream. 11 The spread of infection to the fossa canina usually arises from the maxillary canine teeth or other anterior teeth and the upper premolar teeth, often seen above the buccinator muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The success of treatment requires early recognition, determination of etiological factors, and appropriate medical and surgical management. 5,6 To perform treatment of odontogenic infections, the dentist should understand the terminology regarding infectious diseases and pathophysiology. Odontogenic infections stem from a variety of microbes, such as aerobic bacteria and facultative anaerobes.…”
Section: Introductionmentioning
confidence: 99%